A correlative study of antithyroid antibodies level, thyroid functional status and histological evidence of thyroiditis in patients subjected to thyroidectomy - P., Ravi Desai; Anand, Chetan; C. P., Ganesh Babu; N., Ananthakrishnan (International Surgery Journal, 2017)
Background: There is inadequate data on relationship between histologic thyroiditis, thyroid functional status and antithyroid antibody levels. Aim of the study was to correlate prevalence of antithyroid antibody levels with thyroid functional status and histological evidence of thyroiditis in thyroidectomy specimen. Methods: Thirty-two patients undergoing thyroidectomy were evaluated clinically and with thyroid function tests, preoperative TPOAb and TGOAb, ultrasound neck and FNAC. Histopathological examination to detect histological thyroiditis done. Patients with previous thyroid surgery or on thyroxine, antithyroid drugs, steroids, immune-suppressive drugs were excluded. Results: Overall twenty-five out of thirty-two patients had elevation of one or other thyroid antibody levels (TPOAb- 22/32, TGOAb- 20/32). More than half of the patients with elevated antibodies were euthyroid biochemically, less than quarter each being hypothyroid and hyperthyroid. The incidence of hypothyroid increased in those with elevation of both antibody levels. FNAC reported four as Hashimoto’s thyroiditis. Histology on the other hand showed a primary diagnosis of Hashimoto’s thyroiditis in three, in one each as the secondary diagnosis with papillary carcinoma being the primary diagnosis in one and follicular adenoma in another. Histologic lymphocytic thyroiditis was seen in three cases and found to be always associated with a primary diagnosis such as colloid goitre. Thus, overall five patients had an additional primary diagnosis with thyroiditis being a secondary diagnosis. When histological thyroiditis was correlated with antibodies, it was seen that only seven out of eight with histological thyroiditis had elevated antibody levels. High titters in patients with histological thyroiditis were associated with euthyroid status in two patients and hyperthyroid status in the remaining three. Conclusions: The study found no correlation between clinical and biochemical functional status with clinical examination under diagnosing both hypothyroidism and hyperthyroidism. No definite correlation was noted with mild increases in antithyroid antibody levels and histological thyroiditis, very high values and raises in both TPOAb and TGOAb may suggest histological thyroiditis.